2019
DOI: 10.3390/microorganisms7110508
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Insights into the Stress-Alleviating Property of an Endophytic Bacillus altitudinis WR10 in Wheat under Low-Phosphorus and High-Salinity Stresses

Abstract: An indole–3–acetic acid producing Bacillus altitudinis WR10 was previously isolated from the root of wheat (Triticum aestivum L.). In this study, the strain WR10 was used for relieving abiotic stresses in wheat under low phosphorus and high saline in hydroponic co-culture models. Significantly, strain WR10 improved wheat seed relative germination rate under salinity stress (200/400 mM NaCl) and the root dry weight in wheat seedlings under phosphorus stress (10 μM KH2PO3) when insoluble phosphates are available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…We also found improved P-content in plants treated with bacterial strains compared with uninoculated stressed plants. Yue et al ( 53 ) reported improved productivity of wheat by mediating phosphate availability to the plants under stress conditions through phosphatase enzymes activity. Similarly, NBRI RAR inoculated plants showed approximately similar P level under both control and salinity conditions ( Table 2 ), presumably due to its higher alkaline and acidic phosphatase activity in both conditions (Table S3; https://github.com/ssrivastava-nbri/Supplementary-file/blob/main/Supplementary%20file.pdf ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found improved P-content in plants treated with bacterial strains compared with uninoculated stressed plants. Yue et al ( 53 ) reported improved productivity of wheat by mediating phosphate availability to the plants under stress conditions through phosphatase enzymes activity. Similarly, NBRI RAR inoculated plants showed approximately similar P level under both control and salinity conditions ( Table 2 ), presumably due to its higher alkaline and acidic phosphatase activity in both conditions (Table S3; https://github.com/ssrivastava-nbri/Supplementary-file/blob/main/Supplementary%20file.pdf ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used an endophytic bacterium, B. altitudinis WR10, because it has a strong ability to absorb Fe and improves the ability of wheat to tolerate Fe ( 27 ). In addition, the strain produces siderophores and secretes phytase ( 28 ). These properties made the strain a good candidate for assisting wheat Fe biofortification for three reasons at least.…”
Section: Discussionmentioning
confidence: 99%
“…Phytate is widely recognized as anti-nutritional because of the strong binding potential with minerals, including Fe and Zn ( 47 ). Strain WR10 produces phytases that effectively degrade phytate ( 28 ). Therefore, the content of phytate can be decreased after inoculation with WR10; however, this data suggest that this is not true in grains ( Supplementary Table 4 ), and, as reported in AMF, the positive effect of WR10 on plant Fe accumulation may also be modulated by wheat genotypes, soil pH, texture, and nutrient concentration, as well as agronomic practices, such as N and P fertilization ( 46 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations